Biochemical and histochemical analyses revealing endophytic Alcaligenes faecalis mediated suppression of oxidative stress in Abelmoschus esculentus challenged with Sclerotium rolfsii - Ray, Shatrupa (Plant physiology and biochemistry : PPB, 2016)
Copyright Â© 2016 Elsevier Masson SAS. All rights reserved.